Gestão e financiamento dos planos municipais de educação em Municípios Paulistas: novos/velhos desafios aos dirigentes municipais de educação - SILVA, Leandro Vitoriano da (2018)
This paper is part of studies on the management and financing of basic education, specifically the new National Education Plan and the Municipal Education Plans. The problem raised here is based on the initial observation that the PNE does not foresee a greater linkage of resources to education in the municipal sphere, which, in turn, covers a large part of the compulsory school population, has aroused interest in investigating the implications of the PME (s) in the management and financing of Municipal Education from the perspective of the Municipal Education Directors with the general objective of analyzing the challenges of the Municipal Education Plan in the management and financing of Municipal Education from the perspective of Municipal Teachers. Methodologically, we are based on so-called "meso-analytic" studies, which comprise educational organizations as spaces in which the goals of superior bodies are often reproduced strategically, aiming at fulfilling bureaucratic demands, and it is not possible to guarantee, which ensure their effectiveness, and through bibliographical research, documentary and the transcription of recorded semi-structured interviews was sought to understand the perception of the leaders on the management and financing of education plans. We conclude that the current delineation of Brazilian educational financing, the funding policy, and the small financial contribution of the union to the municipalities do not guarantee even the maintenance of the existing one, and therefore will not guarantee much less the necessary investments for the education sought by the plans.